ANALISIS PROFIL PASIEN DENGAN GANGGUAN JIWA DI RUMAH SAKIT SOEHARTO HEERDJAN - Brian Jodi; Mieke Nurmalasari; Hosizah Hosizah; Witri Zuama Qomarania; Ifah Muzdalifah (Smart Education, 2026)
Abstract: Mental disorders are one of the major health problems that continue to increase in Indonesia and require serious attention. According to Riskesdas (2018), the prevalence of severe mental disorders increased from 1.7 per 1,000 households in 2013 to 7 per 1,000 households in 2018, equivalent to around 450,000 people with severe mental illness, and in 2019 there were still 5,218 cases of severe mental illness under restraint. At Soeharto Heerdjan Hospital, the number of inpatients with mental disorders has shown an increasing trend from 2019 to 2023, rising from 3,068 patients in 2019 to 4,036 patients in 2023, and reaching 4,781 patients in 2024. This study aims to analyze the profile of inpatients with mental disorders at Soeharto Heerdjan Hospital in 2024 based on demographic characteristics, environmental factors, and clinical profiles. This research employed a descriptive quantitative design with a sample of 400 patients drawn from a total population of 4,781 patients. Data were collected through medical record reviews and analyzed using univariate analysis. The results showed that the majority of patients were male (50.2%) and the largest age group was 20–29 years (25.8%). Most patients had no formal education (35.5%) and were covered by BPJS health insurance (89.3%). In terms of environmental factors, the most dominant cause was family conflict (27.8%), followed by socioeconomic factors (20.3%) and the loss of parents/family members (20.0%). The most common diagnosis was paranoid schizophrenia (F20.0) at 40.5%, while the most frequent medical intervention was behavioral therapy (94.23) at 55.3%. The length of stay was most commonly 14 days (12.5%). Keywords: Patient Profile, Mental Disorders, Inpatient Care Abstrak: Gangguan jiwa merupakan salah satu masalah kesehatan yang terus meningkat di Indonesia dan memerlukan perhatian serius. Menurut Riskesdas (2018), prevalensi gangguan jiwa berat meningkat dari 1,7 per 1.000 rumah tangga pada 2013 menjadi 7 per 1.000 rumah tangga pada 2018, setara dengan sekitar 450 ribu ODGJ berat, dan pada 2019 masih tercatat 5.218 ODGJ berat dalam kondisi pasung. Pada rumah sakit Soeharto Heerdjan, jumlah pasien rawat inap dengan gangguan jiwa mengalami peningkatan dari tahun 2019 hingga 2023, yaitu dari 3068 pasien pada 2019 naik menjadi 4036 pasien pada 2023, hingga mencapai 4.781 pasien pada tahun 2024. Penelitian ini bertujuan untuk menganalisis profil pasien rawat inap dengan gangguan jiwa di Rumah Sakit Soeharto Heerdjan tahun 2024 berdasarkan karakteristik demografis, faktor lingkungan dan profil klinis. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan sampel sebanyak 400 pasien dari total populasi 4.781 pasien. Data diperoleh melalui telaah rekam medis dan dianalisis secara univariat. Hasil penelitian menunjukkan bahwa mayoritas pasien berjenis kelamin laki-laki (50,2%) dengan kelompok usia terbanyak 20–29 tahun (25,8%). Sebagian besar pasien tidak menempuh pendidikan formal (35,5%) dan menggunakan jaminan kesehatan BPJS (89,3%). Berdasarkan faktor lingkungan, penyebab dominan adalah konflik keluarga (27,8%), disusul faktor sosial ekonomi (20,3%) dan kehilangan orang tua/keluarga (20,0%). Diagnosis terbanyak adalah skizofrenia paranoid (F20.0) sebesar 40,5% dengan tindakan medis dominan berupa terapi perilaku (94.23) sebesar 55,3%. Lama rawat terbanyak adalah 14 hari (12,5%). Kata Kunci: Profil Pasien, Gangguan Jiwa, Rawat Inap